Proposed Of Indihome Marketing Strategy Through Digital Channel (Case PT. Telkom Indonesia – Witel Jakarta Pusat) - Diani Desi Nugraheni; Ilma Aulia Zaim; Satya Aditya Wibowo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research is motivated by the increasing need for the internet. Internet is a necessity that can be primary needs nowadays. With the advancement of the internet today, digital marketing is an aspect that is very influenced. The high number of internet users in Indonesia creates an opportunity for the development of digital marketing. There has been a significant change in the marketing strategy of both goods and services. With so many Internet Service Provider players currently, IndiHome which is a service product of PT. Telekomunikasi Indonesia (Persero) Tbk, needs to show the strength of its positioning. One of the strengths of IndiHome is that it is the only one that has a Triple Play Service consisting of Internet, Interactive TV and Telephone. Initially, IndiHome was only using conventional channel to sell its product, which is direct offering by Sales Agent to customers, but since August 2022, Witel Jakarta Pusat implementing IndiHome subscriptions via digital channels, can be conducted from Website, Landing Page or Social Media (FB, IG, Twitter). In fact, potential customers feel unfamiliar with how to subscribe to IndiHome via this new channel. This phenomena caused a decrease in IndiHome sales results in September 2022. This research aims to identify the internal and external factors that cause the decline of IndiHome sales in Witel Jakarta Pusat. The methodology used in this research is quantitative method. Data collection technique used in this study were literature study, observation and questionnaire with 140 respondents. The result of this research indicate that Internal and external variables that influenced the decline in IndiHome sales are apart from the fact that IndiHome prices are more expensive than other internet providers, customers find it difficult to subscribe to IndiHome via digital channels so they still choose sales agents as a more convenient way. Customers also find it difficult to get updates regarding subscription stages. Apart from that, customers are also worried about the security of the personal data they upload to the system when making a subscription. The recommended strategy given is to implement Integrated Marketing Communication.